An Investigation into the Perceptions of Veterinarians towards Calf Welfare in New Zealand - Ria van Dyke; Amy Miele; Melanie Connor (Animals, 2021)
Despite recent legislative amendments to address areas of highest risk to the welfare of calves (Bos taurus) in New Zealand, there are prevailing concerns that animal welfare science knowledge has not been adopted in practice. As a part of a larger, nationwide study investigating the perceptions of veterinarians towards calf welfare, the aim of the current work was to investigate the perceptions of veterinarians towards the level of welfare protection afforded to young “bobby” calves in New Zealand. This study also explored concerns for welfare compromise and identified barriers to welfare-related change for calves more generally. An electronic mixed-methods survey was completed by 104 veterinarians registered with the Veterinary Council of New Zealand. The findings revealed that veterinarians strongly disagreed with the specifications of certain calf welfare regulations. Veterinarians also identified areas at highest risk of calf welfare compromise across the production chain and barriers to welfare-related change. These findings demonstrate considerable support among veterinarians for improving the level of welfare protection afforded to calves. Given the discrepancies that exist between the current regulatory regime and veterinary perspectives, the knowledge gained from this study can be used in support of regulatory reform to strengthen calf welfare in practice and policy in New Zealand.